Perbandingan Ekstrak Daun Pepaya (Carica papaya) dan Daun Srikaya (Annona squamosa) Dalam Mematikan Lalat Rumah (Musca domestica) - Kasim, Khiki Purnawati; Zaenab, Zaenab; Riskyah, Nurul (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Makassar, 2024)
The type of fly that is able to reproduce quickly is the house fly (Musca domestica). Flies can act as a cause of digestive diseases such as diarrhea. Data from the South Sulawesi Provincial Health Office in 2020 showed as many as 19,592 cases of diarrhea. The high incidence of diarrheal disease caused by flies so it needs to be controlled. Control of house flies can use vegetable insecticides such as papaya leaves and srikaya leaves which have chemical compounds of flavonoids, alkaloids,S tannins, and saponins. These compounds can cause the death of flies. This study aims to compare the ability of papaya leaf extract (Carica papaya) and srikaya leaves (Annona squamosa) to kill houseflies (Musca domestica). The type of research used is experimental using the spray method. The samples in this study were 20 house flies which were exposed to papaya leaf extract and srikaya leaf extract with concentrations of 35%, 40%, and 45% for 60 minutes with each control on papaya leaves and srikaya leaves. The results showed that the average death rate of house flies on papaya leaves with a concentration of 35% was 14 (70%) while on srikaya leaf it was 16 (80%). At a concentration of 40% on papaya leaves as many as 16 heads (80%) while in srikaya leaves as many as 17 tails (85%). And at a concentration of 45% papaya leaves, the average death rate of flies was 17 (85%) and the srikaya leaf was 18 (90%). As for the conclusion in this study, papaya leaf extract at 40% concentration and 45% effective lethal home fly, while the sri leaf extract was sri at 35% concentration, 40%, and 45% effective off house flies. Keywords : Papaya leaf extract; srikaya leaf exttact; house fly